WHATSAPP REMINDER AS AN EFFORT TO IMPROVE COVID-19 PREVENTION BEHAVIOR - Dani Prastiwi; Isrofah Isrofah; Irine Dwitasari Wulandari; Made Suandika (Viva Medika, 2021)
Abstract. Background. Covid-19 is a health problem in a growing world. On January 30, 2020, WHO designated Covid-19 as a Public Health Emergency of International Concern (PHEIC) or a public health emergency that is troubling the world. Preventive efforts are needed to deal with the Covid 19 pandemic. Objective. To investigated whether there is an effect of using WhatsApp social media on Covid 19 prevention behavior. Method. The approach used was pre-experimental with pre-post test without control group. The data collection technique uses the Google Play Store and online questionnaires. The sample taken was 55 people, which is the minimum sample size based on the conservative assumption that 50% of second semester students have good behavior with a 5% error margin and 95% confidence interval. The analysis technique used is the paired T test. Result. The results showed that the mean value before treatment was 31.00 (7.437) and after treatment was 35.81 (6.003) (Table 5) and the significance was p = 0.000 (p <0.05). Conclusion. There is an effect of Whatsapp Reminder on Covid-19 Prevention Behavior. Keyword : WhatsApp Reminder, Behavior, Covid-19 Prevention